2016
DOI: 10.1007/s11695-016-2182-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of thrombosis and thromboembolic prophylaxis in obesity surgery: data analysis from the German Bariatric Surgery Registry

Abstract: Age, BMI, male gender, and a previous history of VTE are the most important risk factors. The drug of choice for VTE is heparin. LMWH should be given preference over unfractionated heparins due to their improved pharmacological properties, i.e., better bioavailability and longer half-life as well as ease of use. Despite the low incidence of VTE and PE, there is a lack of evidence. Therefore, prospective randomized studies are necessary to determine the optimal VTE prophylaxis for bariatric surgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
2
14
0
3
Order By: Relevance
“…After bariatric surgery, the risk of DVT varies from 0.07% to 2.4% [34][35][36][37][38]. We observed no DVT or PE complications.…”
Section: Discussionmentioning
confidence: 44%
“…After bariatric surgery, the risk of DVT varies from 0.07% to 2.4% [34][35][36][37][38]. We observed no DVT or PE complications.…”
Section: Discussionmentioning
confidence: 44%
“…When comparing different chemoprophylaxis agents, The Michigan bariatric surgery collaborative reported that (LMWH) is more effective the UF in patients undergoing Bariatric surgery without increasing bleeding rate [15]. In addition, LMWH was also reported as the most commonly used agent in both the French national survey and the German Bariatric Surgery Registry data study [3,14]. Furthermore, Nimeri, et al successfully reduced VTE rates after bariatric surgery from 2.2% in 2011 to 0.35% in 2016 after switching from heparin to LMWH, initiating mandatory risk assessment using Caprini scoring for VTE and adopting an aggressive strategy for high-risk patients regarding dosage of LMWH and chemoprophylaxis after discharge [16].…”
Section: Resultsmentioning
confidence: 99%
“…With the rising number of bariatric surgeries, we expect a rise in complications including venous thromboembolism (VTE). The incidence of VTE as reported in the literature ranges from 0.07 to 1.9% at 30 days and rises to 2.1% at 180 days [2][3][4][5][6]. The aim of this survey is to study the incidence of VTE and the practice of VTE thromboprophylaxis in the Middle East region represented by members of the Pan Arab Society of Metabolic and Bariatric Surgery (PASMBS).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the impact of alternative medications is not as well as Heparin. On the other hand, in patients with bypass surgery who have oral medication intolerance or malabsorption, intravenous Heparin administration is much more effective than oral alternative medications (17).…”
Section: Rule Out Other Causes Such As Sepsis Etcmentioning
confidence: 99%